Local ZnCl2 accelerates fracture healing. Issue 6 (26th February 2014) - Wey, Aaron; Cunningham, Catherine; Hreha, Jeremy; Breitbart, Eric; Cottrell, Jessica; Ippolito, Joseph; Clark, Devin; Lin, Hsuan‐Ni; Benevenia, Joseph; O'Connor, J. Patrick; Lin, Sheldon S.; Paglia, David N.
ABSTRACT This study evaluated the effect of local zinc chloride (ZnCl2), an insulin mimetic agent, upon the early and late parameters of fracture healing in rats using a standard femur fracture model. Mechanical testing, radiographic scoring, histomorphometry, qualitative histological scoring, PCNA immunohistochemistry, and local growth factor analysis were performed. Fractures treated with local ZnCl2 possessed significantly increased mechanical properties compared to controls at 4 weeks post fracture. The radiographic scoring analysis showed increased cortical bridging at 4 weeks in the 1.0 (p = 0.0015) and 3.0 (p < 0.0001) mg/kg ZnCl2 treated groups. Histomorphometry of the fracture callus at day 7 showed 177% increase (p = 0.036) in percent cartilage and 133% increase (p = 0.002) in percent mineralized tissue with local ZnCl2 treatment compared to controls. Qualitative histological scoring showed a 2.1× higher value at day 7 in the ZnCl2 treated group compared to control (p = 0.004). Cell proliferation and growth factors, VEGF and IGF‐I, within fracture calluses treated with local ZnCl2 were increased at day 7. The results suggest local administration of ZnCl2 increases cell proliferation, causing increased growth factor production which yields improved chondrogenesis and endochondral ossification. Ultimately, these events lead to accelerated fracture healing as early as 4 weeks post fracture. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:834–841, 2014.